(untitled) (KULT_online, 2013)
In her doctoral thesis, Christine Rath proposes a new perspective on the œuvre of Argentinian author Jorge Luis Borges. He should be read not simply as an author of fantastical tales, Rath argues, but also as an author who deals with problems of history and historiography in his essays and short stories. Rath’s monograph offers this perspective and contextualizes Borges’ texts historically within the Argentinian discourse on historiography. Structuring the text analyses according to thematic foci would probably have simplified reading, but nevertheless the text offers an exciting new perspective on the works of Jorge Luis Borges.